Time to Diagnosis and Treatment of Surgical Site Infections in Foot and Ankle Surgery. (September 2018) - Baranek, Eric S.; Tantigate, Direk; Jang, Eugene; Greisberg, Justin K.; Vosseller, J. Turner
Background: The time at which patients typically present with surgical site infections (SSI) following foot and ankle surgery has not been characterized. The primary aim of this study was to quantify the time to definitive treatment of SSIs. Methods: We performed a retrospective review of 1933 foot and ankle procedures in 1632 patients from 2011 through 2015. Demographic and surgical data were collected. Time to presentation in cases diagnosed with postoperative wound complications or SSIs was analyzed. Wound complications were defined as any case with concerning wound appearance that subsequently resolved with antibiotic therapy alone. SSIs were defined as cases requiring operative irrigation and debridement (I&D) for successful definitive management. Results: A total of 1569 procedures met inclusion criteria, with 17 SSIs (1.1%) and 63 wound complications (4.0%). Time between surgery and definitive treatment in the SSI group was significantly greater than in the wound complication group (28.2 ± 9.1 vs 13.4 ± 4.7 days, P < .00001). Eleven (64.7%) cases in the SSI group failed a trial of antibiotics prior to I&D, and 6 (35.3%) cases did not receive antibiotics prior to I&D. Antibiotic treatment prior to I&D did not significantly decrease the yield of intraoperative wound cultures (70% vs 100%, P = .51). Conclusion: In our cohort of patients, the time to diagnosis and treatment of SSIs was longer than that of wound complications. SSIs requiring operative intervention did not present until an average of 4 weeks after surgery. These data are of some benefit in trying to define and understand SSI. Level of Evidence: Level III, retrospective cohort study.